Parasite strain specificity of bovine cytotoxic T cell responses to Theileria parva is determined primarily by immunodominance. - Taracha, E.L.N.; Goddeeris, B.M.; Teale, A.J.; Kemp, Stephen J.; Morrison, W. Ivan (The American Association of Immunologists, 1995)
The parasite strain specificity of CTL responses to Theileria parva varies among cattle immunized with the same parasite stock. We have investigated the influence of class I MHC on the strain specificity of CTL responses to T. parva in 19 cattle of defined class I phenotype immunized with either of two T. parva populations, in which protection to subsequent reciprocal challenge correlated with CTL strain specificity. In the majority of animals the response was restricted by the products of one MHC haplotype and there was a consistent bias to some haplotypes in preference to others. In 10 of 13 cattle expressing the molecularly defined MHC specificities A10 and KN104 on one haplotype, the CTL response was restricted entirely by this haplotype, thus allowing a precise analysis of the MHC restriction specificities. The MHC restriction specificity and the parasite population used for immunization both influenced the strain specificity of the response. By examining responses in identical twins immunized with different parasites or in animals before and after challenge with heterologous parasites, animals that mounted a strain-specific response to primary infection were shown to be capable of responding to Ags shared by the two parasite populations. These findings indicate that the strain specificity of CTL responses to T. parva is not determined primarily by immune response genes that define the inherent capacity to respond, but rather is a consequence of the response in individual animals being biased toward a limited number of immunodominant peptide-MHC determinants.